Efektivitas Bilingual Dictionary Sebagai Media Pembelajaran Kosakata - Azizah Nurul Aini; Panca Dewi Purwati; Nanik Wijayati; Decky Avrilianda (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
The low mastery of Indonesian vocabulary among class V students in the Ogan Ilir region is caused by the dominance of the use of regional languages in everyday life. This research aims to systematically examine the effectiveness of the Ogan Ilir-Indonesia bilingual dictionary as a vocabulary learning medium to improve the learning outcomes of fifth grade elementary school students. The method used is Systematic Literature Review (SLR) with the PRISMA protocol. Literature was collected from Google Scholar and Publish or Perish, 10 articles were obtained that met the inclusion criteria (published 2021-2026) to be studied in depth. The results of the study show that the use of a Bilingual dictionary has proven effective in increasing students' vocabulary mastery through three main mechanisms: multisensory presentation of information, understanding vocabulary in a meaningful context and increasing students' learning independence. The conclusion of this research confirms that regional language bilingual dictionaries are effective, relevant and contextual learning media in improving fifth grade elementary school students' mastery of Indonesian vocabulary, especially in multilingual environments such as Ogan Ilir.